2020
DOI: 10.3390/nu12010151
|View full text |Cite
|
Sign up to set email alerts
|

Denture Wearing and Malnutrition Risk Among Community-Dwelling Older Adults

Abstract: Most studies have associated denture wearing with a higher risk of malnutrition and lower nutritional intake in the elderly. As the effect of wearing dentures remains debatable, the aim of this study was to determine if older adults wearing dentures have a higher risk of malnutrition. We recruited 294 Japanese community-dwelling adults aged ≥65 years from two elderly welfare centers in Sapporo. The Mini Nutritional Assessment-Short Form (MNA-SF) was used to assess their nutritional status. Their demographic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
2
24
1
Order By: Relevance
“…The improvement of maximum bite force and chewing efficiency may be an important prerequisite for adequate nutrition. The problem of malnutrition has been highlighted recently in some articles that explain how the elderly become malnourished due to problems also related to prosthesis [ 5 , 33 ]. It is clear that these patients require special attention from a nutritionist in order to be able to eat properly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement of maximum bite force and chewing efficiency may be an important prerequisite for adequate nutrition. The problem of malnutrition has been highlighted recently in some articles that explain how the elderly become malnourished due to problems also related to prosthesis [ 5 , 33 ]. It is clear that these patients require special attention from a nutritionist in order to be able to eat properly.…”
Section: Discussionmentioning
confidence: 99%
“…This type of diet results in malnutrition and increased risk of frailty development. Some studies [ 5 , 6 ] showed a relation between teeth loss and body mass index (BMI), a measure of body fat based on height and weight. In addition, such food regimes may favor the insurgence of diabetes and other metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PM is a building block of skeletal muscles and other cells, which directly depends on nutrition (or malnutrition) and adaptation to physical activity (or hypokinesia). Both nutrition and physical activity initiate the synthesis of proteins, whereby the type of nutrition and physical activity or exercise define weather PM will increase or remain the same [ 27 , 45 , 46 ]. However, because PM is an integral part of body composition and can remain the same even if the body composition changes (i.e., body fat increases), its relative (%) amount seems more valid for comparison between adults of different age.…”
Section: Discussionmentioning
confidence: 99%
“…As per earlier literature available, intake of fruit, vitamins, dietary fibre, vegetable, and minerals are associated with dentation. It was found that individuals wearing dentures face difficulties in eating and thus been able to consume important nutrients as they have less food choices 2,3 . Dairy products such as milk and products made of milk are found to be linked to plays a preventive role in development of dental caries as higher level of calcium and protein is present in milk 4 .…”
Section: Introductionmentioning
confidence: 99%